Investigating deep-learning NLP for automating the extraction of oncology efficacy endpoints from scientific literature - Gendrin-Brokmann, Aline; Harrison, Eden; Noveras, Julianne; Souliotis, Leonidas; Vince, Harris; Smit, Ines; Costa, Francisco; Milward, David; Dimitrievska, Sashka; Metcalfe, Paul; Louvet, Emilie (Intelligence-based medicine, 2024)
Benchmarking drug efficacy is a critical step in clinical trial design and planning. The challenge is that much of the data on efficacy endpoints is stored in scientific papers in free text form, so extraction of such data is currently a largely manual task. Our objective is to automate this task as much as possible. In this study we have developed and optimised a framework to extract efficacy endpoints from text in scientific papers, using a machine learning approach. Our machine learning model predicts 25 classes associated with efficacy endpoints and leads to high F1 scores (harmonic mean of precision and recall) of 96.4 % on the test set, and 93.9 % and 93.7 % on two case studies. These methods were evaluated against – and showed strong agreement with – subject matter experts and show significant promise in the future of automating the extraction of clinical endpoints from free text. Clinical information extraction from text data is currently a laborious manual task which scales poorly and is prone to human error. Demonstrating the ability to extract efficacy endpoints automatically shows great promise for accelerating clinical trial design moving forwards. [Display omitted] •A fine-tuned deep-learning model was used to extract efficacy endpoints.•The model shows high performance in predicting efficacy endpoints.•High scores were achieved on two literature review case studies.•This shows great promise for accelerating clinical trial design moving forwards.